More on Result Involution Graphs - Aubad, Ali Abd; Salih, Haval M. Mohammed (Iraqi Journal of Science, 2023)
The result involution graph of a finite group , denoted by  is an undirected simple graph whose vertex set is the whole group  and two distinct vertices are adjacent if their product is an involution element. In this paper, result involution graphs for all Mathieu groups and connectivity in the graph are studied. The diameter, radius and girth of this graph are also studied. Furthermore, several other graph properties are obtained.